Book Review: AL-BUTI AND THE SYRIAN REVOLUTION by Bachar Bakour - Altabaa, Homam; Iskandar, Iylia Marsya (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
Bachar Bakour, Al-Buti and the Syrian Revolution. Islamic Book Trust, Petaling Jaya, Selangor, 2020. 349 pp. ISBN-10: 9670526817; ISBN-13: 978-9670526812. Bachar Bakour’s Al-Buti and The Syrian Revolution underscores, through balanced academic analysis, a critical juncture in the history of contemporary Syria, where a horrific war claimed the lives of thousands and displaced millions of others in a calamitous manner around the world. The author has thoroughly examined al-Buti’s views on the Syrian revolution and the ensuing war. His insights into al-Buti’s legal and maqasidic thinking were based on interviews, document analysis and his personal experience as a young Syrian scholar. The book provides critical insights into al-Buti’s positions on the Syrian Revolution and political Islam, Islamist movements and his relationship with the ruling family in Syria.